ANALISIS PERAN GURU DALAM MEMBANGUN KEPERCAYAAN DIRI SISWA UNTUK MENGATASI KECEMASAN MATEMATIKA DIKELAS 4 SD - Nisa, Zahara Fakhrun; Alani, Nabella; Mutaqin, Ejen Jenal (De Fermat : Jurnal Pendidikan Matematika, 2026)
Mathematics is a fundamental subject that plays an important role in developing logical, systematic, and critical thinking skills. However, in elementary school mathematics learning, a common problem encountered is mathematics anxiety, which is characterized by feelings of fear, hesitation, and lack of confidence when students solve problems. This study aims to analyze the role of teachers in building students’ self-confidence to overcome mathematics anxiety in fourth-grade elementary school. This study employed a qualitative approach with a descriptive design. The research subjects consisted of one fourth-grade teacher and five students as informants. Data were collected through participatory observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results showed that teachers play important roles as motivators, facilitators, and guides. As motivators, teachers provide encouragement and positive reinforcement to increase students’ confidence. As facilitators, teachers provide concrete learning media and actively engage students in the learning process, which helps them understand concepts and reduce anxiety. As guides, teachers provide individual assistance to students who experience difficulties, making them feel more comfortable and confident in learning mathematics. The practical implication of this study indicates that the optimal implementation of teachers’ roles as motivators, facilitators, and guides can enhance students’ self-confidence and help reduce mathematics anxiety in the learning process